Bahasa Inggris - Fitriyah, Tina; Priyadi, Ira Hasti; Purnamawati, Anni Muslimah (Shafin: Sharia Finance and Accounting Journal, 2025)
This study aims to examine the effect of Book tax difference (BTD) and Thin Capitalization on Tax avoidance in Indonesian manufacturing companies, motivated by the persistent inconsistency in the findings of previous research. This research uses a quantitative explanatory approach. The sample consists of manufacturing companies in the health and technology sectors listed on the Indonesia Stock Exchange for the 2022-2024 period, selected through purposive sampling. Data were analyzed using multiple linear regression. The results show that Book tax difference and Thin capitalization do not have a significant effect on Tax avoidance, either simultaneously or partially. The implication of this finding is that stakeholders and regulators should not rely solely on BTD and Thin capitalization as primary indicators of aggressive tax practices. The novelty of this research lies in providing recent empirical evidence from a specific contemporary context that challenges the significance of these two common proxies, suggest that other factors are more influential. Future research is encouraged to explore other determinants such as corporate governance mechanisms.